Analysis of decision parameters for route plans and their importance for sustainability: An exploratory study using the TOPSIS technique - Alice Vasconcelos Nobre; Caio Cézar Rodrigues Oliveira; Denilson Ricardo de Lucena Nunes; André Cristiano Silva Melo; Gil Eduardo Guimar\~aes; Rosley Anholon; Vitor William Batista Martins (Logistics, 2022)
Background: This study aimed to identify the most widespread performance objectives for the vehicle routing problem, the degree of comparative importance attributed to each of these performance objectives in the opinion of professionals in the logistics area working in Brazil and also relate them to aspects of sustainability considering environmental, economic and social issues. Methods: To this end, a literature review was carried out in the area and a survey was developed with professionals through a structured questionnaire. The collected data were treated using the TOPSIS multi-criteria technique. Results: The results indicate that the performance objectives in route plans "level of service", "total number of vehicles" and "total distance travelled" are the ones that, in the opinion of the professionals participating in the research, have greater importance in the planning and elaboration of plan routes and that such objectives directly impact the sustainable results of a given organization. Conclusions: The results can serve as a basis for researchers in the area who aim to broaden the debates on this topic and for logistics operations managers who work directly with planning and elaboration of route plans and who aim to make their operations more sustainable. Therefore, this research addresses the literature gap by identifying which performance objectives should be considered in the elaboration of route plans and how they relate to sustainability guidelines. It is noteworthy that no other study with a similar objective was identified in the literature.
Keywords: 650; vehicle routing problem; sustainability; TOPSIS